PENGHORMATAN PLURALITAS HUKUM MASYARAKAT DALAM BINGKAI HUKUM NASIONAL SEBAGAI SARANA MENEGUHKAN INTEGRASI BANGSA - imam ropii (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2017)
Abstract Legal plurality of Indonesian society is an objective condition which requires an understanding and the high regard of all components of the nation. Plurality law into capital social and culture very valuable to be accommodated and managed by the state . NRI Constitution of 1945 has given place and guarantee the existence and development of legal plurality of society. Recognition , supervision and legal plurality appreciation society has been importand instrument in efforts to reinforce national integration. Keywords : plurality laws , national laws , national integration.